Perceived support at work after critical incidents and its relation to psychological distress: a survey among prehospital providers. Issue 12 (21st October 2017) - Gouweloos-Trines, Juul; Tyler, Mark P; Giummarra, Melita J; Kassam-Adams, Nancy; Landolt, Markus A; Kleber, Rolf J; Alisic, Eva
Abstract : Introduction: Prehospital providers are at increased risk for psychological distress. Support at work after critical incidents is believed to be important for providers, but current guidelines are in need of more scientific evidence. This study aimed to investigate: (1) to what extent prehospital providers experience support at work; (2) whether support at work is directly associated with lower distress and (3) whether availability of a formal peer support system is related to lower distress via perceived colleague support. Methods: This cross-sectional study surveyed prehospital providers from eight western industrialised countries between June and November 2014. A supportive work environment was operationalised as perceived management and colleague support (Job Content Questionnaire), availability of a formal peer support system and having enough time to recover after critical incidents. The outcome variable was psychological distress (Kessler 10). We conducted multiple linear regression analyses and mediation analysis. Results: Of the 813 respondents, more than half (56.2%) were at moderate to high risk of psychological distress. Participants did not consistently report support at work (eg, 39.4% were not aware of formal peer support). Perceived management support (b (unstandardised regression coefficient)=−0.01, 95% CI −0.01 to 0.00), having enough time to recover after critical incidents (b=−0.07, 95% CI −0.09 to −0.04) and perceived colleague support (b=−0.01, 95% CI −0.01 to 0.00) were related to lower distress. Availability of formal peer support was indirectly related to lower distress via increased perceived colleague support (β=−0.04, 95% CI −0.02 to −0.01). Conclusions: Prehospital providers at risk of psychological distress may benefit from support from colleagues and management and from having time to recover after critical incidents. Formal peer support may assist providers by increasing their sense of support from colleagues. These findings need to be verified in a longitudinal design.